PV energy penetration in Saudi Arabia: current status, residential, and commercial users, local investment, use in modern agriculture - Muhammad Zubair (International Journal of Sustainable Engineering, 2024)
Saudi Arabia is the largest country in the Middle East with huge solar energy resources but has achieved minimal adoption of photovoltaic energy systems (PV). This study investigates the potential of PV systems to address pressing challenges, including water scarcity and agricultural unemployment. This study addresses the deployment of PV in contemporary agriculture such as aquaponics and hydroponics to promote sustainable water, energy, and agricultural practices. Scrutinising national goals for PV energy against ground realities. The buyback tariff, interest rates of loans, and potential future power price increases are simulated to find suitable rates to encourage PV adoption. The current government grid purchase price is 1.87 cents USD/kWh, while the national grid selling price is 4.8 cents USD/kWh. Small-scale PV plants offer local investors passive income streams if financial institutes can offer these projects at lower interest rates. Investigating the country’s educational sector reveals the need for an overhaul in technical education for solar energy systems. The simulation shows that PV use in agriculture is economically feasible for large loads even with buyback rates as low as 1.87 cents USD/kWh. This research contributes by emphasising local involvement and proposing financial mechanisms, government reforms, and sustainable agricultural development in the region.